2015
DOI: 10.1002/2015gl063827
|View full text |Cite
|
Sign up to set email alerts
|

Eddy stirring and horizontal diffusivity from Argo float observations: Geographic and depth variability

Abstract: Stirring along isopycnals is a significant factor in determining the distribution of tracers within the ocean. Salinity anomalies on density surfaces from Argo float profiles are used to investigate horizontal stirring and estimate eddy mixing lengths. Eddy mixing length and velocity fluctuations from the ECCO2 global state estimate are used to estimate horizontal diffusivity at a 300 km scale in the upper 2000 m with near‐global coverage. Diffusivity varies by over two orders of magnitude with latitude, longi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

24
101
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(126 citation statements)
references
References 53 publications
24
101
0
1
Order By: Relevance
“…In addition, the global mean of the vertical heat flux that is due to isopycnal mixing shows a subsurface maximum, being close to 1.5 W m 22 , in ECCO v4r1 around 500-m depth. This value is consistent with an independent calculation based on the estimates of isopycnal diffusivity from Cole et al (2015) and the World Ocean Atlas (WOA) climatology. A more detailed comparison between the along-isopycnal heat flux in ECCO v4r1 and that implied by the isopycnal diffusivity from Cole et al (2015) will be presented in a separate study.…”
supporting
confidence: 89%
“…In addition, the global mean of the vertical heat flux that is due to isopycnal mixing shows a subsurface maximum, being close to 1.5 W m 22 , in ECCO v4r1 around 500-m depth. This value is consistent with an independent calculation based on the estimates of isopycnal diffusivity from Cole et al (2015) and the World Ocean Atlas (WOA) climatology. A more detailed comparison between the along-isopycnal heat flux in ECCO v4r1 and that implied by the isopycnal diffusivity from Cole et al (2015) will be presented in a separate study.…”
supporting
confidence: 89%
“…For vertical turbulent and molecular mixing, measurements of T, S, and velocities at vertical spatial scales of centimeters are required throughout the entire water column and at horizontal spacing spanning the entire ocean, a suite of measurements not easy to collect (Killworth, 1998). In the absence of direct observations, mixing fields are often inferred from indirect observations and theories (e.g., Kunze et al, 2006;Whalen et al, 2012;Cole et al, 2015). At high latitudes, lack of knowledge in the three-dimensional distribution of these mixing fields is one of the primary reasons the Arctic Ocean's mean horizontal and vertical hydrographic structure is not well reproduced in numerical models (Holloway et al, 2007;Nguyen et al, 2011;Ilicak et al, 2016).…”
Section: Itp Data As Constraints For Estimating Ocean Model Parametersmentioning
confidence: 99%
“…A number of diffusivity estimates other than Okubo's have been made for the Gulf Stream extension region (e.g., Zhurbas and Oh, 2004;LaCasce, 2008;Rypina et al, 2012;Abernathey and Marshall, 2013;Klocker and Abernathey, 2014;or Cole et al, 2015). These estimates are based on surface drifters (Zhurbas and Oh, 2004;LaCasce, 2008;Rypina et al, 2012), satellite-observed velocity fields (Abernathey and Marshall, 2013;Klocker and Abernathey, 2014;Rypina et al, 2012), and Argo float observations (Cole et al, 2015), and they use either the spread of drifters or the evolution of simulated or observed tracer fields to deduce diffusivity.…”
Section: Application To the Altimetric Velocities In The Gulfmentioning
confidence: 99%
“…These estimates are based on surface drifters (Zhurbas and Oh, 2004;LaCasce, 2008;Rypina et al, 2012), satellite-observed velocity fields (Abernathey and Marshall, 2013;Klocker and Abernathey, 2014;Rypina et al, 2012), and Argo float observations (Cole et al, 2015), and they use either the spread of drifters or the evolution of simulated or observed tracer fields to deduce diffusivity. The resulting diffusivities are spatially varying and span 2 orders of magnitude, from 2 × 10 4 m 2 s −1 in the most energetic regions in the immediate vicinity of the Gulf Stream and its extension, to 10 3 m 2 s −1 in less energetic areas, to 200 m 2 s −1 in the coastal areas of the Slope Sea.…”
Section: Application To the Altimetric Velocities In The Gulfmentioning
confidence: 99%
See 1 more Smart Citation